IUEE
EU
Sign in
Ask The Question
English
French
Spanish
Portuguese
Polish
Romanian
Mathematics
SylvieLoughrey
Feb 4, 2018, 12:18:50 PM
2
Solve: K= 2(11 - k) + 14
+0
(
1
) Answers
arleth
Feb 4, 2018, 9:05:29 PM
k=2(11-k)+14 k=22-2k+14 2k+k=22+14 3k=36 k=36/3 k=12
Add answer
Sign in
Sign up
Related Questions
Solve: K= 2(11 - k) + 14
Solve for k. -11 = k 3 + -12
Solve for k: 2k(7-5k)+11=6k+3(k^2-1) with work please.
Solve 2x-11 = k for x
k+7d/2 = -3d +5 solve for k
k - 5 = 3/14 A) k = 4 1/14 B) k = 5 3/14 C) k = 5 2/9
solve the inequality k+8-2(k-12)>0
What is this? Solve 4x+11=k for x
k/8 + 1 - k = 19 solve
what is the answer to 14